ANALISIS KASUS PUTUSAN MAHKAMAH AGUNG NO. 439 K/PID/2010 ATAS TUDUHAN PENIPUAN YANG DILAKUKAN OLEH OKNUM NOTARIS - EVA ARTHA SITANGGANG (PREMISE LAW JURNAL, 2016)
A notary who runs the office of notary can not be punished by or under the act of doing so by law, namely committing mengkonstatir purpose / intention of the parties that require a legal action they do can be proved by authentic act, as long as the implementing office has followed procedures prescribed by the Act (see in particular Article 16 and Article 17 of Law No. 30 of 2004 relating to the obligations and restrictions. Notary deeds which can be classified as a criminal act of fraud is the act of using a fake name (naam valsche), using dignity/false position (valsche hoedanigheid), using the ruse (listige kunstgreoen) and a series of lies (zamenweefsel van verdichtsels). The consideration of the Supreme Court in the Ruling No. 439 K/Pid/2010 on charges of fraud committed by the Notary is accused BN has violated the provisions of Article 378 of the Criminal Code jo. Article 55 paragraph (1) to 1 of the Criminal Code. Protection for the notary on charges of criminal fraud in their official duty is A Notary can not be held criminal liability on the deed he made when he was doing his duty in accordance with the laws and regulations relating to its duties as a notary, it is legitimized in Article 266 the Criminal Code. A notary can not be convicted of criminal on Article 266 of the Criminal Code because it has done its job properly. The position of a Notary Public in Article 266 of the Penal Code is the one who told (manus ministra), and in the criminal law, a person who is asked for doing something cannot be asked for his responsibility for what he has done. Keywords: Notary, Responsibility for position, Fraud